Tafsir Tarbawi: Guru Menurut Pandangan Qs. Hud 11: 88 - Rahmad Ridwan; Radinal Mukhtar Harahap (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
Islamic education is conceptually an education that refers to clear and well-established foundations and resources. Experts say that the first source is the Koran in addition to other sources of the US-Sunnah, words of friends, the benefit of the people, traditions or customs of the society and the thought of the experts in the sphere of Islamic thought. Tafseer In this matter is domiciled as the explanatory of the first source. This article – using the method of interpretation Tarbawi, will attempt to elaborate the interpretation of the QS. Hud 11:88 to give the idea that teachers are not simple professions that can be done simply as well. There is a requirement of deep competence regarding acquired-perennial knowledge on him. These terms are being ruled out in a teacher's sincere nature. Its task and function are improvement (Ishla h) By observing the Khair, Shawab and Mashlahah. In its overall context, the teacher's position is philosophically, as the prophet, and worthy to be examined in its relevance to contemporary conditions.